Cover Picture: Plasma Process. Polym. 10∕2016. Issue 10 (October 2016) - Alvarez, Rafael; Garcia‐Valenzuela, Aurelio; Lopez‐Santos, Carmen; Ferrer, Francisco J.; Rico, Victor; Guillen, Elena; Alcon‐Camas, Mercedes; Escobar‐Galindo, Ramon; Gonzalez‐Elipe, Agustin R.; Palmero, Alberto
Abstract : Front Cover: The Authors present a technique to grow thin films with composition raging from pure metallic to full stoichiometric by magnetron sputtering, using the oblique angle configuration. The film stoichiometry is tuned by tilting the substrate with respect to the target, and using low amounts of reactive gases. This method has been tested by growing TiO2 thin films, achieving growth rates 400% higher than using the classical non‐oblique approach. Further details can be found in the article by R. Alvarez et al.on page 960 .